Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

Solve for x.
2x = 15 + x
x = -15
x = 15
x = -15/2
x = 15/2 **Weegy:** x = -5 **User:** When negative five is subtracted from a number the result is 10. Find the number.
15
5
-5
-15 **Weegy:** When negative five is subtracted from a number the result is 10. Find the number. 15 5 -5 -15
The answer is -5 (More)

Question

Updated 63 days ago|3/19/2015 8:55:50 AM

2 Answers/Comments

2x = 15 + x

2x-x = 15

x= 15 .

2x-x = 15

x= 15 .

Added 63 days ago|3/19/2015 8:54:59 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by sujaysen [3/19/2015 9:01:25 AM]

Which of the following represents "the difference between a number and eight is twenty-two"?
8 - N = 22
N - 8 = 22
8 - 22N **Weegy:** The answer is: b.N - 8 = 22 **User:** Which of the following represents "five times the sum of a number and fifteen is fifty"?
5(N + 15) = 50
5N + 15N = 50
5N + 15 = 50 **Weegy:** A.5(N + 15) = 50. Five times the sum of a number N and 15 is equal to 50. **User:** Which of the following represents "the difference between ten and a number is the sum of eight and a number"?
A: 10 - N(8 + N)
B: 8 - N = 10 + N
C: 10 - N = 8 + N **Weegy:** 3-3 = 0 **User:** Which of the following represents "the difference between ten and a number is the sum of eight and a number"?
10 - N(8 + N)
8 - N = 10 + N
10 - N = 8 + N **Weegy:** 3-3 = 0 **User:** Which of the following represents "a number less ten is twenty-two"?
10 - N = 22
N - 22 = 10
N - 10 = 22 **Weegy:** The answer is N - 10 = 22 (More)

Question

Expert Answered

Updated 3/22/2014 4:47:01 AM

1 Answer/Comment

10 - N = 8 + N represents "the difference between ten and a number is the sum of eight and a number".

Added 3/22/2014 4:47:01 AM

Solve for x.
3(x + 2) + 4(x - 5) = 10
x = 36/7
x = 24/7
x = 16/7
x = 9/7 **Weegy:** 3-3 = 0 **User:** Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1)
x = 0
x = 1/4
x = 1/2
x = 1 **Weegy:** 3-3 = 0 (More)

Question

Updated 319 days ago|7/6/2014 6:02:03 AM

2 Answers/Comments

3(x + 2) + 4(x - 5) = 10

3x + 6 + 4x - 20 = 10;

3x + 4x = 10 - 6 + 20;

7x = 24;

x = 24/7

3x + 6 + 4x - 20 = 10;

3x + 4x = 10 - 6 + 20;

7x = 24;

x = 24/7

Added 319 days ago|7/6/2014 6:00:18 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [7/6/2014 2:06:37 PM]

Solve for x.
7(x + 1) = 21
x = 2
x = 20/7
x = 22/7
x = 4 User: Simplify the given equation.
5x + 2(x - 3) = -2(x - 1)
7x - 6 = -2x - 2
7x - 6 = -2x + 2
7x - 3 = -2x - 1 **Weegy:** 7x+18-3x+39.Hence 4x+57=0.so x=57/4 **User:** Solve for x.
7(x + 2) = 6(x + 5)
x = -44
x = -16
x = 16
x = 44 **Weegy:** D.x = 44 **User:** Solve for x.
7(x - 3) + 3(4 - x) = -8
x = 1/4
x = 25/10
x = -16/19
x = -41/10
Question #8MultipleChoice Score:
Solve for x.
7(3 - x) = 8(4 - 2x)
x = -53/23x = -5/9x = 11/23x = 11/9
Question #9MultipleChoice Score:
Solve for x.
5(x + 1) = 4(x + 8)
x = 7x = 17x = 27x = 37
Question #10MultipleChoice Score:
Solve for x.
3(x + 2) = 12
x = 2x = 3x = 4x = 6
Question #11MultipleChoice Score:
Solve for x.
4(x + 2) = 48
x = 6x = 7x = 10x = 14
Question #12MultipleChoice Score:
Solve for x.
13(x - 3) = 39
x = 1x = 4x = 6x = 10
Question #13MultipleChoice Score:
Simplify the given equation.
6 - (3x + 10) + 4(2 - x) = 15
4 - 7x = 154 - 4x = 1512 - 7x = 15
**Weegy:** hat depends on whether you mean (2/3)x or 2/(3x).
will do them both
For (2/3)x = 8, x = 8?(3/2) = 4?3 = 12
If you meant 2/(3x) = 8 then cross-multiply like this:
2 .... 8
- - = - -
3x ...1
2(1) = 8(3x)
2 = 24x so x = 2/24 = 1/12 (More)

Question

Updated 357 days ago|5/29/2014 9:31:12 AM

3 Answers/Comments

7(x + 1) = 21

7x + 7 = 21

7x = 21 - 7

7x = 14

x = 14/7 = 2

7x + 7 = 21

7x = 21 - 7

7x = 14

x = 14/7 = 2

Added 357 days ago|5/29/2014 9:29:25 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [5/29/2014 9:29:55 AM]

5x + 2(x - 3) = -2(x - 1)

5x + 2x - 6 = -2x + 2

7x - 6 = -2x - 2

5x + 2x - 6 = -2x + 2

7x - 6 = -2x - 2

Added 357 days ago|5/29/2014 9:30:35 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [5/29/2014 9:32:12 AM]

7(x + 2) = 6(x + 5)

7x + 14 = 6x + 30

7x - 6x = 30 - 14

x = 16

7x + 14 = 6x + 30

7x - 6x = 30 - 14

x = 16

Added 357 days ago|5/29/2014 9:31:12 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [5/29/2014 9:32:24 AM]

Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1)
x = 0
x = 1/4
x = 1/2
x = 1 **Weegy:** ab - 9 = c is the answer. (More)

Question

Updated 2/18/2014 2:57:34 PM

1 Answer/Comment

5(x - 3) + 4(x + 3) = 3(x - 1)

(5x - 15) + (20x + 12) = 3x - 3

25x - 3 = 3x - 3

25x - 3x = -3 + 3

22x = 0

x = 0

(5x - 15) + (20x + 12) = 3x - 3

25x - 3 = 3x - 3

25x - 3x = -3 + 3

22x = 0

x = 0

Added 2/18/2014 2:57:33 PM

This answer has been confirmed as correct, not copied, and helpful.

21,026,724 questions answered

There are no comments.